2014
DOI: 10.1371/journal.pone.0091032
|View full text |Cite
|
Sign up to set email alerts
|

Hands as Sex Cues: Sensitivity Measures, Male Bias Measures, and Implications for Sex Perception Mechanisms

Abstract: Sex perceptions, or more particularly, sex discriminations and sex categorisations, are high-value social behaviours. They mediate almost all inter-personal interactions. The two experiments reported here had the aim of exploring some of the basic characteristics of the processes giving rise to sex perceptions. Experiment 1 confirmed that human hands can be used as a cue to an individual’s sex even when colour and texture cues are removed and presentations are brief. Experiment 1 also showed that when hands ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“…Bülthoff, 2012;Cellerino, Borghetti, & Sartucci, 2004) that has also been reported in chimpanzees (de Waal & Pokorny, 2008). A similar 'male bias' has also been found for body shape (Johnson, Iida, & Tassinary, 2012), hands (Gaetano, van der Zwan, Blair, & Brooks, 2014) and biological motion (Troje, Sadr, Geyer, & Nakayama, 2006). It has been suggested that, in the history of humans, misclassifying a man as female has generally proved to be potentially more dangerous than misclassifying a woman as male (Armann & Bülthoff, 2012).…”
Section: Bias In the Perception Of A Person's Sexsupporting
confidence: 54%
“…Bülthoff, 2012;Cellerino, Borghetti, & Sartucci, 2004) that has also been reported in chimpanzees (de Waal & Pokorny, 2008). A similar 'male bias' has also been found for body shape (Johnson, Iida, & Tassinary, 2012), hands (Gaetano, van der Zwan, Blair, & Brooks, 2014) and biological motion (Troje, Sadr, Geyer, & Nakayama, 2006). It has been suggested that, in the history of humans, misclassifying a man as female has generally proved to be potentially more dangerous than misclassifying a woman as male (Armann & Bülthoff, 2012).…”
Section: Bias In the Perception Of A Person's Sexsupporting
confidence: 54%
“…The other effect that manifests in these data is the so-called “male bias.” Here, for both the structure (upright and inverted) and kinematics (upright only) continua, point-light walkers that actually carried weak female cues were misperceived as male. The male bias previously has been reported to manifest not only for point-light walkers ( Troje, Sadr, Geyer, & Nakayama, 2006 ; Troje & Szabo, 2006 ), but also for hands ( Gaetano, Brooks, & van der Zwan, 2012 ; Gaetano, Brooks, van der Zwan, Hayward, & Oxner, 2013 ; Gaetano, van der Zwan, Blair, & Brooks, 2014 ), and for faces ( Hess, Adams, Grammer, & Kleck, 2009 ). That it manifests here in both conditions suggests that for point-light walkers at least, the bias is driven by both structure and kinematics processing mechanisms.…”
Section: Discussionmentioning
confidence: 90%
“…A robust male-bias can also emerge as a side-effect when participants categorize faces ( Armann & Bülthoff, 2012 ; Johnson, Freeman, & Pauker, 2012 ; Wild et al, 2000 ), and may be enhanced by the emotionality of the faces ( Bayet et al, 2015 ; Hess, Adams, Grammer, & Kleck, 2009 ). Independent of cues like emotion or pigmentation, ambiguous face ( Davidenko, 2007 ), body ( Johnson, Iida, & Tassinary, 2012 ) and hand ( Gaetano, van der Zwan, Blair, & Brooks, 2014 ) shapes, as well as point-like walkers ( Schouten, Troje, Brooks, van der Zwan, & Verfaillie, 2010 ) also have produced the male-bias.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this shortcoming is that participants are generally only provided bipolar choice options: male versus female . In one study ( Gaetano et al, 2014 ), participants were asked to indicate yes or no whether a certain stimulus was male, and separately whether a stimulus was female, instead of the classical male-female categorization task. As a consequence, participants were more likely to assign male gender when targeting male hands, as well as less likely to assign female gender when searching for female hands.…”
Section: Introductionmentioning
confidence: 99%